Germline RET Leu56Met Variant Is Likely Not Causative of Multiple Endocrine Neoplasia Type 2 - Anna Reimer Hansen (Frontiers Media S.A., 2021)
Activating variants in the receptor tyrosine kinase REarranged during Transfection (RET) cause multiple endocrine neoplasia type 2 (MEN 2), an autosomal dominantly inherited cancer-susceptibility syndrome. The variant c.166C>A, p.Leu56Met in RET was recently reported in two patients with medullary thyroid cancer (MTC). The presence of a pheochromocytoma in one of the patients, suggested a possible pathogenic role of the variant in MEN 2A. Here, we present clinical follow up of a Danish RET Leu56Met cohort. Patients were evaluated for signs of MEN 2 according to a set of predefined criteria. None of the seven patients in our cohort exhibited evidence of MEN 2. Furthermore, we found the Leu56Met variant in our in-house diagnostic cohort with an allele frequency of 0.59%, suggesting that it is a common variant in the population. Additionally, none of the patients who harbored the allele were listed in the Danish MTC and MEN 2 registries. In conclusion, our findings do not support a pathogenic role of the Leu56Met variant in MEN 2.